TEMPORARY REMOVAL: Effects of flow lamination on aerosolized drug delivery through spatial barriers - Haroutunian, GGreg; Tsaghikian, Ashot; Soherwardy, Amenah; Zheng, Haiyan; Mosoian, Arevik (International journal of pharmaceutics, 2025)
The publisher regrets that this article has been temporarily removed. A replacement will appear as soon as possible in which the reason for the removal of the article will be specified, or the article will be reinstated. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/policies/article-withdrawal.